Sensitivity of osteosarcoma cells to HDAC inhibitor AR-42 mediated apoptosis. Issue 1 (December 2017) - Murahari, Sridhar; Jalkanen, Aimee; Kulp, Samuel; Chen, Ching-Shih; Modiano, Jaime; London, Cheryl; Kisseberth, William
Abstract Background Osteosarcoma (OS) is the most common primary bone tumor in both humans and dogs and is the second leading cause of cancer related deaths in children and young adults. Limb sparing surgery along with chemotherapy has been the mainstay of treatment for OS. Many patients are not cured with current therapies, presenting a real need for developing new treatments. Histone deacetylase (HDAC) inhibitors are a promising new class of anticancer agents. In this study, we investigated the activity of the novel HDAC inhibitor AR-42 in a panel of human and canine OS cell lines. Methods The effect of AR-42 and suberoylanilide hydroxamic acid (SAHA) alone or in combination with doxorubicin on OS cell viability was assessed. Induction of histone acetylation after HDAC inhibitor treatment was confirmed by Western blotting. Drug-induced apoptosis was analyzed by FACS. Apoptosis was assessed further by measuring caspase 3/7 enzymatic activity, nucleosome fragmentation, and caspase cleavage. Effects on Akt signaling were demonstrated by assessing phosphorylation of Akt and downstream signaling molecules. Results AR-42 was a potent inhibitor of cell viability and induced a greater apoptotic response compared to SAHA when used at the same concentrations. Normal osteoblasts were much less sensitive. The combination of AR-42 with doxorubicin resulted in a potent inhibition of cell viability and apparent synergistic effect. Furthermore, we showed that AR-42 and SAHA induced cell death via the activation of the intrinsic mitochondrial pathway through activation of caspase 3/7. This potent apoptotic activity was associated with the greater ability of AR-42 to downregulate survival signaling through Akt. Conclusions These results confirm that AR-42 is a potent inhibitor of HDAC activity and demonstrates its ability to significantly inhibit cell survival through its pleiotropic effects in both canine and human OS cells and suggests that spontaneous OS in pet dogs may be a useful large animal model for preclinical evaluation of HDAC inhibitors. HDAC inhibition in combination with standard doxorubicin treatment offers promising potential for chemotherapeutic intervention in both canine and human OS.